Tax Avoidance and the Financial Structures of Non-Resident Controlled Companies in New Zealand - Smith, Andrew; Dunmore, Paul (School of Management Working Papers, 1996)
For many years the New Zealand tax regime for non-resident investors has been unfavourable due to high effective tax rates imposed on income earned by New Zealand resident companies that are controlled by non-resident investors. This gave rise to significant incentives for non-resident investors to avoid New Zealand tax by adopting income shifting arrangements such as transfer pricing and thin capitalisation. Despite the incentives to adopt such income shifting arrangements, until 1996 New Zealand tax law has contained few provisions to attack such arrangements. Transfer pricing rules until 1996 have been largely weak and there were no explicit provisions in force to address thin capitalisation. Given this environment it was assumed that non-resident controlled companies (NRCCs) would adopt income shifting strategies to avoid New Zealand tax. A financial database of NRCCs operating in New Zealand was obtained for the period 1983-1992. Tests were applied to determine whether NRCCs had higher debt/equity ratios than comparable resident-controlled companies (RCCs), thereby implying that thin capitalisation had been adopted by NRCCs to avoid New Zealand tax. Results obtained showed that NRCCs did have higher debt/ equity ratios than comparable RCCs but often the debt owed by NRCCs was non interest-bearing. Thus it cannot be concluded that NRCCs used thin capitalisation to avoid New Zealand tax in this period. Evidence was obtained that NRCCs may have used manipulative transfer pricing rather than thin capitalisation to shift profits.